A new analytic tool for assessing the impact of the US Food and Drug Administration regulatory actions. Issue 3 (15th November 2022) - Lu, Christine Y.; Hou, Laura; Kolonoski, Joy; Petrone, Andrew B.; Zhang, Fang; Corey, Catherine; Huang, Ting‐Ying; Bradley, Marie C.
Abstract: Purpose: Develop and test a flexible, scalable tool using interrupted time series (ITS) analysis to assess the impact of Food and Drug Administration (FDA) regulatory actions on drug use. Methods: We applied the tool in the Sentinel Distributed Database to assess the impact of FDA's 2010 drug safety communications (DSC) concerning the safety of long‐acting beta2‐agonists (LABA) in adult asthma patients. We evaluated changes in LABA use by measuring the initiation of LABA alone and concomitant use of LABA and asthma controller medications (ACM) after the DSCs. The tool generated ITS graphs and used segmented regression to estimate baseline slope, level change, slope change, and absolute and relative changes at up to two user‐specified time point (s) after the intervention. We tested the tool and compared our results against prior analyses that used similar measures. Results: Initiation of LABA alone declined among asthma patients aged 18–45 years before FDA DSCs (−0.10% per quarter; 95%CI: −0.11% to −0.09%) and the downward trend continued after. Concomitant use of LABA and ACM was stable before FDA DSCs. After FDA DSCs, there was a small trend decrease of 0.006% per quarter (95% CI, −0.008% to −0.003%). We found similar results among those aged 46–64 years and patients with poorly‐controlled asthma. Our results were consistent with previous studies, confirming the performance of the new tool. Conclusions: We developed and tested a reusable ITS tool in real‐world databases formatted to the Sentinel Common Data Model that can assess the impact of regulatory actions on drug use.